'My husband is living like a dead person': explaining women portage labour in Ibadan urban market. Issue 3 (3rd July 2022) - Tade, Oludayo
ABSTRACT: African urban market spaces are heavily congested and mostly unfavourable for mobility. Understanding this difficult terrain, human porters facilitate navigation of difficult layouts. They negotiate with buyers and carry their loads to the bus stops or car parks. Load carriers are of both sexes but very little has been empirically done to understand women as porters and the dynamics of their work as well as its organization. In this study, we interviewed 30 female porters in Bodija food market in Ibadan. Findings show that due to their fragile nature, light luggages are carried by women unlike men who carry bags of beans and rice. Variations exist in resumption and closing among women porters. There was seasonality in portage labour with high earnings at month end, weekends and during festivities.